2022
DOI: 10.3390/molecules27134058
|View full text |Cite
|
Sign up to set email alerts
|

How Curcumin Targets Inflammatory Mediators in Diabetes: Therapeutic Insights and Possible Solutions

Abstract: Diabetes mellitus is a multifactorial chronic metabolic disorder, characterized by altered metabolism of macro-nutrients, such as fats, proteins, and carbohydrates. Diabetic retinopathy, diabetic cardiomyopathy, diabetic encephalopathy, diabetic periodontitis, and diabetic nephropathy are the prominent complications of diabetes. Inflammatory mediators are primarily responsible for these complications. Curcumin, a polyphenol derived from turmeric, is well known for its anti-oxidant, anti-inflammatory, and anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 138 publications
0
12
0
Order By: Relevance
“…The antioxidant, anti-inflammatory, and anticancer properties of curcumin have made it a potential nutritional supplement [ 208 , 209 , 210 , 211 ]. The anti-inflammatory role of curcumin has been well established in recent decades [ 196 , 211 , 212 , 213 , 214 , 215 , 216 ]. For instance, it has been reported that curcumin can potentially reduce the activity of several inflammation-related transcription factors, including NF-κB, AP-1, signal transducer and activator of transcription (STAT), and hypoxia-inducible factor-1 (HIF-1).…”
Section: Effects Of Polyphenols On Altered Intercellular Communicationmentioning
confidence: 99%
“…The antioxidant, anti-inflammatory, and anticancer properties of curcumin have made it a potential nutritional supplement [ 208 , 209 , 210 , 211 ]. The anti-inflammatory role of curcumin has been well established in recent decades [ 196 , 211 , 212 , 213 , 214 , 215 , 216 ]. For instance, it has been reported that curcumin can potentially reduce the activity of several inflammation-related transcription factors, including NF-κB, AP-1, signal transducer and activator of transcription (STAT), and hypoxia-inducible factor-1 (HIF-1).…”
Section: Effects Of Polyphenols On Altered Intercellular Communicationmentioning
confidence: 99%
“…Curcumin is a main active ingredient of the Chinese herbal medicine Curcuma longa which possesses strong pharmacological properties such as antioxidant, antiapoptotic and neuroprotective effects in various diseases [ 21 , 22 , 23 ]. It has been reported that excessive ROS production and lipid peroxidation could be suppressed by curcumin intervention [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits diabetes-related enzymes, including α-glucosidase and aldose reductase, while increasing the activity of antioxidant enzymes. Curcumin improves insulin sensitivity by reducing ERK/c-Jun N -terminal kinase-mediated phosphorylation of insulin-resistant cells and activating the phosphatidylinositol 3-kinase-Akt-GSK3B signaling pathway [ 158 ]. The anti-diabetic effect of curcumin possibly comes from its ability to suppress OS and the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-diabetic effect of curcumin possibly comes from its ability to suppress OS and the inflammatory process. It targets inflammatory pathways and modulates/normalizes inflammatory mediators (e.g., TNF–α, INF-γ), systemic inflammatory biomarkers (e.g., RANTES), and other inflammatory cytokines [ [158] , [159] , [163] ]. Curcumin regulates the expression of keap1 and restores the function of NRF2, promoting insulin sensitivity and redox homeostasis [ 158 , 160 , 161 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation